Global behavior of integral transforms. (26th June 2006) - Vindas, Jasson; Estrada, Ricardo
Abstract : We obtain global estimates for various integral transforms of positive differentiable functions that satisfy inequalities of the typec 1 f ( x ) / x ≤ − f ' ( x ) ≤ c 2 f ( x ) / x, forx > 0 .